Lights, camera, action: the role of editing and framing on the processing of filmed events. Issue 5 (17th August 2020) - Magliano, Joseph P.; Kurby, Christopher A.; Ackerman, Thomas; Garlitch, Sydney M.; Stewart, J. Mac
ABSTRACT: Filmmakers use various cinematic techniques in an effort to guide attention to certain aspects of these events. The present study was conducted to investigate how framing and editing can guide viewers' attention toward character actions during event segmentation. Participants watched and segmented a movie that simultaneously showed two actors engaged in two related activities. Participants watched one of three versions of the movie: Static center version that did not foreground any character; Static off-center version that foregrounding one of the characters, and an edited version with a mix of shots that foregrounding both characters. Participants engaged in an event partonomy task in which they were asked to identify the boundaries between the events that were depicted in the movie. After watching the movie, they were asked to recall the events. The results showed converging evidence between the event segmentation and recall data, which both indicated that cinematic devices affect the perception and memory of the event structure depicted in the film.